ANALYSIS OF STUDENT DIFFICULTIES IN EDUCATION PHILOSOPHY MATERIALS IN UISU ENGLISH LITERATURE PRODI - Nurismilida Nurismilida (JURNAL HANDAYANI PGSD FIP UNIMED, 2018)
Abstract: Analysis of Student Learning Difficulties in Educational Philosophy Material at UISU English Literature Study Program. The large number of students who have difficulty in studying the philosophy of education is the main reason that makes writers interested in this problem. The subjects used for the study were the 2017 UISU English Literature Students with 28 people. The method used is the questionnaire method in the form of a questionnaire. The results of the study show that the difficulties of students in the philosophy of education subject are influenced by several factors, namely factors from lecturers, students, learning time, learning materials used and the influence of educational philosophy courses on the education system.Keywords : Learning Difficulties, Educational Philosophy, Questionnaire MethodAbstrak : Analisis Kesulitan Belajar Mahasiswa Pada Materi Filsafat Pendidikan Di Prodi Sastra Inggris UISU. Banyaknya mahasiswa yang kesulitan dalam mempelajari filsafat pendidikan adalah alasan utama yang membuat penulis tertarik dengan masalah ini. Subjek yang dijadikan untuk penelitian yaitu Mahasiswa Sastra Inggris 2017 UISU dengan jumlah 28 orang. Metode yang digunakan adalah metode kuisioner dalam bentuk angket. Diperoleh hasil bahwa kesulitan mahasiswa dalam mata kuliah filsafat pendidikan dipengaruhi oleh beberapa faktor yaitu faktor dari dosen, mahasiswa, waktu pembelajaran, bahan pembelajaran yang digunakan dan pengaruh dari mata kuliah filsafat pendidikan terhadap sistem pendidikan.Kata Kunci : Kesulitan Belajar, Filsafat Pendidikan, Metode Kuisioner